The Impact of Managerial Creative Capabilities on Task Performance: Evidence from Saudi Arabian Companies - DAHININE, Benameur (Journal of Ecohumanism, 2024)
Purpose: This research examines the impact of managerial creative capabilities on task performance, addressing a significant gap in the current literature. By integrating the dynamic capability approach, this study considers managerial creativity as a dynamic capability that enables managers to enhance efficiency and foster innovation, ensuring organizational competitiveness in fast-evolving contexts. Design/methodology/approach: A quantitative approach was employed, utilizing a questionnaire distributed to 457 middle and senior managers across 87 organizations in Saudi Arabia. The study adopted a snowball sampling technique to ensure industry and organizational diversity. Findings: The results validate our hypotheses, emphasizing managerial creative capabilities’ impact on task performance. The ability to sense creative opportunities significantly enhances task efficiency, aligning with prior studies on innovation’s role in opportunity recognition. The ability to seize these opportunities translates them into actionable tasks, reinforcing the importance of timely decision-making and execution. Most notably, the study reveals that managerial creative reconfiguring exerts the strongest influence on task performance. This highlights the critical role of resource reconfiguration in leveraging opportunities, confirming its status as a cornerstone of dynamic capabilities. Originality/value: This research advances the understanding of managerial creativity by framing it as a dynamic capability that influences task performance. The findings provide actionable insights for managers to balance creativity with productivity, fostering flexibility and innovation. By addressing an underexplored area, this study contributes to the development of practical strategies for sustainable organizational success.